2019
DOI: 10.24042/albayan.v11i2.5175
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Teaching Material Arabic Speaking Skills in Higher Education

Abstract: Research objective is to providing an insight into the characteristics of Arabic language teaching materials in higher education in Indonesia. This research was conducted by examining a variety of literature relating to teaching materials and Arabic speaking skills. The research method applied survey, involving 97 students from the Arabic Language Education Study Program in several universities in Indonesia and structured interviews with lecturers who supported Arabic speaking skills. The procedure taken are 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…When explaining Arabic language materials, the Indonesian sentences used need to be clear to avoid misconceptions. This aligns with Pribadi's (2014) (Zulharby et al, 2019) (Hafidz Zaid, 2020 argument that unclear Indonesian usage in Arabic language instruction may create communication gaps with the audience. Improper word arrangement can result in flat and rigid narrative sentences, diminishing the interest of students to delve deeper into the subject.…”
Section: Introductory Language For Comprehensionsupporting
confidence: 82%
“…When explaining Arabic language materials, the Indonesian sentences used need to be clear to avoid misconceptions. This aligns with Pribadi's (2014) (Zulharby et al, 2019) (Hafidz Zaid, 2020 argument that unclear Indonesian usage in Arabic language instruction may create communication gaps with the audience. Improper word arrangement can result in flat and rigid narrative sentences, diminishing the interest of students to delve deeper into the subject.…”
Section: Introductory Language For Comprehensionsupporting
confidence: 82%
“…However, in these findings, we found that there were significant differences in perceptions between teachers and students about Arabic speaking skills assessment techniques. This indicates that there is a discrepancy between what teachers do and what students feel [12], [15], [40]. These findings also indicate that teachers use only the most easily applied assessment techniques [36], [41], [42].…”
Section: Discussionmentioning
confidence: 99%
“…When someone speaks, the listener will give a specific response to the personality and attitude [6]. The achievement of students' speaking skills in Arabic is still relatively low [7]- [9], including among universities [10]- [12]. This is because the speaking skills of non-Arabic Arabic learners are faced with various problems, especially in linguistic and non-linguistic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics resulting from the teaching materials that have been developed are a combination of language skills, the provision of basic grammatical and pronunciation concepts that are by the needs of speaking Arabic in national and international contexts, teaching materials have the value of local wisdom, the teaching materials learned can build the skills needed in the 21st century (Khawarizmi et al, 2021). Because teaching materials taken from the Middle East can cause gaps in the achievement of Arabic language skills for beginners, such as the lack of phonetic aspects being taught, monotonous forms of exercise, directing students to memorize, and types of dialogue that are not by student culture in Indonesia (Zulharby, Zulharby, Rasyid, & Nuruddin, 2019;Tajuddin, Kamal, & Zuryati, 2019).…”
Section: B) Large Trial Of Product and Final Revision Of Productmentioning
confidence: 99%